EFFECT OF MOTHERHOOD HEALTH PROMOTION DEVELOPMENT MEDIA TRAINING ON HEALTH PROMOTORâS KNOWLADGE AND SKILL IN BANYUMAS DISTRICT - Ayunin, Elia Nur (Kesmas Indonesia, 2018)
High maternal mortality has indirect relation influenced by motherhood education. Motherhood education has inderect reletion to the ability of the health promotor is design the media for dissemination the information. In order to improve ability of heatlh promotorâs, traning development on motherhood health promoting media is required. The purpose of this study was to know the effect of motherhood health promotion media development training on health promotorâs knowledge and skill in the district Banyumas. The method was a quasi experimental with one-group pretest and posttest design. Sampel which were 32 people obtained by using purposive sampling technique. Analysis of data used is wilcoxcon test. The results comparisons between the pretest and posttest I showed there were significant differences in maternal health knowledge (P=0,003) and skill of making media (P=0,000). The results comparisons between the postest I and posttest II showed there were significant difference in maternal health knowlegde (P=0,002) and skill of making media (P=0,011). The suggested that training to use in increasing their knowledge and skills in designing another health promotion media.